A SURVEY ON BRAIN TUMOR DETECTION BASED ON IMAGE PROCESSING TECHNIQUES USING MACHINE LEARNING ALGORITHM - Srinivas, C S; M , Balasaraswathi (International Journal of Psychosocial Rehabilitation, 2020)
The development of irregular tissue in a particular place is called a tumor. The human body contains a large volume of cells. The normal procedure is that the old cells are replaced by new cells. But the rarely normal function of this procedure is changed due to any unwanted growth of cells. The tumor is identified in an earlier stage by using image processing techniques. It is a very challenging work for current researchers. For detecting a tumor in the brain, the MRI images are given as input. In this paper, an important classification and SVM classifier techniques are used to identify the brain tumor in the beginning stages. If the tumor is detected in the early stages, it is mostly curable. The main benefit of this concept is to detect the position of the tumor and easily calculate the size of the tumor.